2011
DOI: 10.1093/cid/ciq006
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Swine-Origin Influenza: 1976 and 2009

Abstract: I am in a unique situation, having been involved in 2 major US public health events resulting from novel swine-origin influenza viruses. In 1976, I was Director of the Center for Disease Control (CDC, the name of the agency at the time) when a new influenza virus, characterized as an influenza A(H1N1) swine virus, was isolated from military recruits at Fort Dix, New Jersey. Subsequently, I led the CDC through the US response to this outbreak, which culminated in the decision to implement the swine flu vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…However, the emergence of novel influenza A (H1N1) virus among humans in April 2009 caught the world by surprise. For years, public health professionals had been preparing for a scenario in which influenza A (H5N1) would emerge from Southeast Asia [34,35], only to confront instead a novel influenza A (H1N1) virus of swine origin in San Diego County, California [7,8]. Pandemic planning scenarios assumed a “worst case scenario” with a high level of illness severity, with some time from recognition of the pandemic to widespread geographic dissemination [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the emergence of novel influenza A (H1N1) virus among humans in April 2009 caught the world by surprise. For years, public health professionals had been preparing for a scenario in which influenza A (H5N1) would emerge from Southeast Asia [34,35], only to confront instead a novel influenza A (H1N1) virus of swine origin in San Diego County, California [7,8]. Pandemic planning scenarios assumed a “worst case scenario” with a high level of illness severity, with some time from recognition of the pandemic to widespread geographic dissemination [35].…”
Section: Discussionmentioning
confidence: 99%
“…For years, public health professionals had been preparing for a scenario in which influenza A (H5N1) would emerge from Southeast Asia [34,35], only to confront instead a novel influenza A (H1N1) virus of swine origin in San Diego County, California [7,8]. Pandemic planning scenarios assumed a “worst case scenario” with a high level of illness severity, with some time from recognition of the pandemic to widespread geographic dissemination [35]. Although the planning scenarios differed from the actual events in 2009, the public health efforts that were initiated prior to the 2009 pandemic had substantial benefits that were not fully realized until 2009.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision to initiate and then withdraw a mass vaccination campaign was regarded by some as a public health failure [3] , resulting in sustained and unforeseen consequences on vaccine-seeking behavior, and loss of public confidence in decision-making. Firsthand accounts [4] – [8] and historical assessments [9] , [10] have emphasized the difficulty of compressed decision-making under conditions of uncertainty. While improvements in near real-time vaccine safety surveillance now allow earlier detection of vaccine safety signals [11] , [12] , the need to act in the context of scientific uncertainty has not changed.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Beyond the US, the World Health Organization declared the world unsuited to respond to future emergencies without advancements in global preparedness through a suite of strategies which include research, reliance on a multisectoral approach, strengthened health care delivery systems, economic development in low and middle income countries, and overall improved health status. 4 In a comparison of the 2009-2010 H1N1 pandemic to the 1976 H1N1 pandemic, Sencer describes lessons from the 2 events including managing expectations and risk communication, the importance of accurate surveillance, and flexible planning and decision making 5 Both research and organizations' self-examination (via "hot wash" activities * ) have shown that having planning models in place to address continuity of operations, managing temporary staff, building community partnerships, streamlining communications, and improving vaccination strategies and logistics are important ways to augment pandemic influenza plans. 6,7 Though much has been written about retrospective lessons from previous pandemic responses, we are not aware of any studies examining what actual changes have been made to policy, infrastructure, practice, and relationships that reflect lessons learned from challenges encountered.…”
Section: Introductionmentioning
confidence: 99%